Methods of Clinical Epidemiology - Doi, Suhail A. R.; Williams, Gail M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
(3z(BMethods of Clinical Epidemiology(3y (Bserves as a text on methods useful to clinical researchers. It provides a clear introduction to the common research methodology specific to clinical research for both students and researchers. This book sets out to fill the gap left by texts that concentrate on public health epidemiology and focuses on what is not covered well in such texts. The four sections cover methods that have not previously been brought together in one text and serves as a second level textbook of clinical epidemiology methodology. This book will be of use to postgraduate students in clinical epidemiology as well as clinical researchers at the start of their careers.s
Preface -- PART I: Clinical Agreement -- 1.Clinical Agreement in Qualitative Measurements. S.Vanbelle. 2.Clinical Agreement in Quantitative Measurements. A.Indrayan -- 3.Disagreement Plots and the Intra-class Correlation in Agreement Studies. S.A.R. Doi -- 4.The Coefficient of Variation as an Index of Measurement Reliability. O.Shechtman -- PART II: Diagnostic Tests -- 5.Using and Interpreting Diagnostic Tests with Dichotomous or Polychotomous Results. C.Baicus -- 6.Using and Interpreting Diagnostic Tests with Quantitative Results. S.A. Doi -- 7.Sample Size Considerations for Diagnostic Tests. R.K.Malhotra -- 8.An Introduction to Diagnostic Meta-analysis. M.Nieves Plana, V.Abraira and J.Zamora -- 9.Health Technology Assessments of Diagnostic Tests. R.Esmail -- PART III: Modeling Binary and Time-To-Event Outcomes -- 10.Modelling Binary Outcomes. G.M. Williams and R.Ware -- 11.Modelling Time-to-event Data. G.M. Williams and R.Ware -- PART IV: Systematic Reviews and Meta-analysis -- 12.Systematic Reviewing. J.Clark -- 13.Quality Assessment in Meta-analysis. M.Dreier -- 14.Meta-analysis I. S.A.R. Doi and J.J. Barendregt -- 15.Meta-analysis II. A.A. Onitilo, S.A. R. Doi and J.J. Barendregt -- Appendix: Stata codes -- Index.
Keywords: Medicine; Epidemiology; Bioinformatics; Statistical methods; Biology -- Data processing; Medicine & Public Health; Epidemiology; Computer Appl. in Life Sciences; Biostatistics; Bioinformatics